2017
DOI: 10.1007/s00204-017-1993-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of silica nanoparticles: an update

Abstract: Large-scale production and use of amorphous silica nanoparticles (SiNPs) have increased the risk of human exposure to SiNPs, while their health effects remain unclear. In this review, scientific papers from 2010 to 2016 were systematically selected and sorted based on in vitro and in vivo studies: to provide an update on SiNPs toxicity and to address the knowledge gaps indicated in the review of Napierska (Part Fibre Toxicol 7:39, 2010). Toxicity of SiNPs in vitro is size, dose, and cell type dependent. SiNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
333
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(343 citation statements)
references
References 135 publications
6
333
1
3
Order By: Relevance
“…However, based on an estimation derived from human tolerable levels, Murugadoss et al concluded that relevant SAS concentrations for in vitro assays should not exceed 384 µg/cm 2 [26]. Although it is generally difficult to extrapolate the in vitro dose to the in vivo status, SAS concentrations used in this study (ranging from 2 µg/cm 2 to 80 µg/cm 2 ) could be considered as physiologically relevant.…”
Section: Discussionmentioning
confidence: 93%
“…However, based on an estimation derived from human tolerable levels, Murugadoss et al concluded that relevant SAS concentrations for in vitro assays should not exceed 384 µg/cm 2 [26]. Although it is generally difficult to extrapolate the in vitro dose to the in vivo status, SAS concentrations used in this study (ranging from 2 µg/cm 2 to 80 µg/cm 2 ) could be considered as physiologically relevant.…”
Section: Discussionmentioning
confidence: 93%
“…29 Studies of nonporous SNPs 30,31 and mesoporous SNPs 32,33 showed a size-, shape-, and chemistry-dependent biodistribution. In the future, the assessment of the degradation, 34 clearance, 30 and toxicity 35,36 of Hb-loaded SNPs will be an important step for the development of adsorbed hemoglobinbased oxygen carriers.…”
Section: Resultsmentioning
confidence: 99%
“…28 Great attention has been paid to the use of polymeric nanoparticles (NPs) as delivery vehicles for lung-disease drugs, and some studies have suggested that nanocarriers can significantly enhance antifibrotic drug efficacy. [29][30][31][32] Local delivery of biodegradable PD NPs has exhibited high dispersibility and suitable distribution for inhalation therapy, with sustained lung delivery and enhanced antifibrotic efficacy. 29 Nevertheless, to succeed pulmonary drug-delivery must overcome several critical and unique challenges, including toxicological evaluation of materials and mucociliary clearance.…”
Section: Introductionmentioning
confidence: 99%
“…29 Nevertheless, to succeed pulmonary drug-delivery must overcome several critical and unique challenges, including toxicological evaluation of materials and mucociliary clearance. [30][31][32] Compared with inhalation, the intravenous route is valid and efficient, which ensures the accuracy of individual doses. The nanoscale dimensions of drug-delivery systems allow entry into blood circulation directly, avoiding degradation by enzymes on the alveolar membrane.…”
Section: Introductionmentioning
confidence: 99%